The influence of a human resource strategy to the function of human resource processes in small and medium-sized enterprises (SMEs) - Vrchota, Jaroslav; Rehor, Petr (Serbian Journal of Management, 2019)
The human resources management strategy is currently considered one of the most important elements of a corporate strategy, mainly because its main goal is to work with people as the most important capital of each organization. Without people, the organization is unable to meet its goals. A well-prepared HR strategy and an action plan for its implementation enables an organization to effectively plan and manage individual processes to support the organization’s goals and to respond flexibly to any change. The paper deals with a sub-research of the management of small and medium-sized enterprises in the Czech Republic. It is focused on the use of HR strategy in SMEs management and the assessment of the significance of HR process. Data were gathered as questionnaires and interviews from 290 enterprises operating in the Czech Republic. The research was done in 2016. Unfortunately, the HR strategy is defined by 2/5 of small and medium-sized enterprises in the Czech Republic. Based on statistics analysis, the authors proved a weak relation between HR strategy and the function of human resource processes.